2018
DOI: 10.1186/s13068-018-1333-3
|View full text |Cite
|
Sign up to set email alerts
|

Altering the linker in processive GH5 endoglucanase 1 modulates lignin binding and catalytic properties

Abstract: BackgroundThe non-productive adsorption of cellulases onto lignin in biomass is a key issue for the biofuel process economy. It would be helpful to reduce the inhibitory effect of lignin on enzymatic hydrolysis by engineering weak lignin-binding cellulases. Cellulase linkers are highly divergent in their lengths, compositions, and glycosylations. Numerous studies have revealed that linkers can facilitate optimal interactions between structured domains. Recently, efforts have focused on the contributions and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…Due to their dual functions, processive endoglucanases, coupled with a β-glucosidase, may be sufficient for the degradation of cellulose . To date, several studies were focused on structural features and biochemical characteristics of processive endoglucanases. Efforts to immobilize such an enzyme for improved stability and reusability are, however, still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their dual functions, processive endoglucanases, coupled with a β-glucosidase, may be sufficient for the degradation of cellulose . To date, several studies were focused on structural features and biochemical characteristics of processive endoglucanases. Efforts to immobilize such an enzyme for improved stability and reusability are, however, still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In general, many cellulases are typical multimodule enzymes and contain a catalytic domain (CD) and a carbohydrate-binding module (CBM) connected by a linker peptide. 30,67,68 The flexibility of the linker peptide has a significant effect on the catalytic mechanism. 30,[69][70][71][72] For example, Boisset et al proposed that Cel45 from Humicola insolens, which features a flexible linker, may exhibit an inchworm-like mechanism for hydrolysis.…”
Section: Effects Of Linker Region On Processive Bindingmentioning
confidence: 99%
“…30,67,68 The flexibility of the linker peptide has a significant effect on the catalytic mechanism. 30,[69][70][71][72] For example, Boisset et al proposed that Cel45 from Humicola insolens, which features a flexible linker, may exhibit an inchworm-like mechanism for hydrolysis. The linker region (residues 441-457) in Cel9G shows some rigidity because of a lack of glycine residues.…”
Section: Effects Of Linker Region On Processive Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…9,12,13 Furthermore, the bulk of research has primarily concentrated on exploring the contributions and mechanisms of various carbohydrate-binding modules concerning the processivity of such enzymes. 7,11,13,20 Currently, engineering studies of processive EGs mainly focus on specific spatial regions within the protein such as the active site or the substrate binding pocket. Several studies reported that specific aromatic amino acids in the substrate binding pocket may improve binding affinity and facilitate processivity via carbohydrate-π interactions.…”
Section: ■ Introductionmentioning
confidence: 99%